Student's Rationality for Continuing Education in Equivalency Program (Case Study at Sabilum Najjah Community Learning Center) - Hasna Bararah Mufidah; Joan Hesti Gita Purwasih; Mochamad Ilham Akbar; Dhanu Dewantara Aji (Universitas Negeri Padang, 2022)
Education is an effort made by individuals to acquire knowledge in the learning process. The number of people in Malang City who drop out of school and cannot complete their education is a problem for the community and the government. One solution for the community to be able to complete their education is to attend a non-formal school, one of the non-formal schools in Malang that has been recognized and trusted, namely PKBM Sabilun Najjah. This research is a descriptive qualitative research with the aim of knowing the rationality of learners in continuing their education at PKBM Sabilun Najjah and the expectations of learners in continuing their education in PKBM. Based on the results of the study, learners continue their education at PKBM Sabilun Najjah not only to get a diploma, but learners have special reasons, namely PKBM Sabilun Najjah has adequate facilities and programs, has official and accredited permits, school distance is close to home, and there are family relationship between learners and tutors. The hope of learners after completing their education at PKBM Sabilun Najjah is that they hope to create a business, get relationships, complete requirements from agencies, and get recognition by completing their education at PKBM Sabilun Najjah.Keywords: PKBM, Rational Action, Equality Program